FIELD WORK: ETNOGRAFI DAN ETNOGRAFI DIGITAL - Mita Rosaliza; Hesti Asriwandari; Indrawati Indrawati (Jurnal Ilmu Budaya, 2023)
The presence of digital platforms increasingly permeates contemporary everyday culture, necessitating a re-evaluation of observational studies on social and cultural phenomena. Traditional qualitative research methods that rely on physical locations face challenges in the era of digital platforms. This article aims to explain the use of ethnography and digital ethnography in fieldwork, combining classic ethnographic methods with participant observations in locations where digital platforms are utilized. Technical exploration can uncover social and cultural assumptions embedded in interactions and interviews, as well as how their accessibility can create symbolic meanings. Meanwhile, participant observation focuses on the perspectives of digital platform users within a community. Referring to pioneering works in the field of "digital ethnography," this article critically explores the potential and challenges posed by new technologies that warrant attention. It can be concluded that a balanced combination of physical and digital ethnography not only provides researchers with diverse and intriguing methods but also allows for a better appreciation of respondents' voices. The development of digital ethnography as a research methodology, along with the challenges encountered in addressing classical concepts of fieldwork, participation, and representation, creates opportunities for digital ethnographers to gain professional recognition in conducting research related to society and culture.